Optimisation of the zinc sulphate turbidity test for the determination of immune status. (13th February 2016) - Hogan, I.; Doherty, M.; Fagan, J.; Kennedy, E.; Conneely, M.; Crowe, B.; Lorenz, I.
Abstract : Failure of passive transfer of maternal immunity occurs in calves that fail to absorb sufficient immunoglobulins from ingested colostrum. The zinc sulphate turbidity test has been developed to test bovine neonates for this failure. The specificity of this test has been shown to be less than ideal. The objective was to examine how parameters of the zinc sulphate turbidity test may be manipulated in order to improve its diagnostic accuracy. One hundred and five blood samples were taken from calves of dairy cows receiving various rates of colostrum feeding. The zinc sulphate turbidity test was carried out multiple times on each sample, varying the solution strength, time of reaction and wavelength of light used and the results compared with those of a radial immunodiffusion test, which is the reference method for measuring immunoglobulin concentration in serum. Reducing the time over which the reaction occurs, or increasing the wavelength of light used to read the turbidity, resulted in decreased specificity without improving sensitivity. Increasing the concentration of the zinc sulphate solution used in the test was shown to improve the specificity without decreasing sensitivity. Examination of the cut‐off points suggested that a lower cut‐off point would improve the performance.